B Bahasa arab kunci memahami agama - Nur Anisah, Mu'in Abdullah (Bashrah, 2024)
The majority of Indonesia's population is Islamic. The Qur'an and Hadith, written entirely in Arabic, became the guidelines for the life of Muslims. Therefore, Muslims need to learn Arabic in order to more easily understand the content of the Holy Quran and Hadith and deepen its religious aspects. The types of research used are descriptive and qualitative, providing a clear picture of the data available in this area. Since Arabic is the key to understanding religion, this study aims to find out what are the benefits of Arabic for Muslims in understanding religion. The Quran and Hadith are the main sources of information for Muslims. Therefore, if Muslims master Arabic well, by themselves they will more easily understand the Koran and the Hadith. This will also prevent misunderstandings in understanding the content of the Koran. The Quran and the Hadith itself Arabic is not only the language of Muslims, but also the language of Allah's choice, just like the language of the Koran. Keywords: Arabic, Key, Religion